Evaluation of the XVI dual registration tool for image-guided radiotherapy in prostate cancer - Sousa, Filipa (Tech Innov Patient Support Radiat Oncol, 2021)
PURPOSE: To compare the reliability and the required time for two cone-beam CT (CBCT) registration methods for prostate irradiation (PI) and prostate bed irradiation (PBI). MATERIAL AND METHODS: Two-hundred treatment fractions (in 10 PI and 10 PBI patients) were reanalyzed, using two CBCT registration methods: (1) a combination of an automated chamfer matching (CM) with manual matching (MM), and (2) the automated XVI dual registration tool (DRT). Bland-Altman 95% Limits of Agreement (LoA) were used to assess agreement with manual registration by Radiation Oncologists. RESULTS: All 95% LoA for CM + MM were ≤ 0.33 cm. For DRT, several 95% LoA were notably larger than the predefined clinical threshold of 0.3 cm: −0.47 to +0.25 cm (PI) and −0.36 to +0.23 cm (PBI) for the superior-inferior direction and −0.52 to +0.24 cm (PI) and −0.38 to +0.31 cm (PBI) for the anterior-posterior direction. For PI, the average time required was 33 s with CM + MM versus only 18 s with DRT (p = 0.002). For PBI, this was 13 versus 19 s, respectively (p = 0.16). CONCLUSION: For PI, DRT was significantly faster than CM + MM, but the accuracy is insufficient to use without manual verification. Therefore, manual verification is still warranted, but could offset the time benefit. For PBI, the CM + MM method was faster and more accurate.